EDUKASI KOMUNIKASI EFEKTIF TERHADAP ANAK PADA ENTITAS MASYARAKAT DESA - Qurrota Ainiy Rezita Siswoyo; M.Arizal Nur Rochman; Muhammad Jawahirul Mubarroq; Harizma .; Nashrudin Latif (LPPM Universitas Islam Darul 'Ulum Lamongan, 2023)
The basis for forming a child's character starts with how to apply an effective pattern of environmental communication. In its application, problems arose among the village partners, both teachers, parents and children regarding the implementation of child care. The aim of this activity is to increase knowledge and understanding of communication patterns in the surrounding environment in implementing character education for children. Activities are carried out in the form of implementing the Real Work Lecture (KKN) program through mentoring with parents, the community and students according to scientific fields/work programs ranging from education, parenting, health, security and creative-productive. The result of this community service activity is that it can increase the community's knowledge and understanding of children's communication patterns in character education from the perspective of various work programs. The implication of community service activities (KKN) is that work program materials and practices can help village managers/officials apply the principles of parenting in their social interaction activities so that parents and children can overcome the problems of violence against children, malnutrition and increase their creativity together.